Securing banking activity through specific provisions (loan loss reserves): an empirical analysis of Polish listed banks 2011-2019 - Chaikovska, Ivanna (Zabezpieczenie działalności bankowej przez rezerwy celowe: analiza empiryczna polskich banków giełdowych w latach 2011-2019, 2022)
The author analysed specific provisions (loan loss reserves) as a hedging tool against expected losses in banking activity. The aim of the article was to conduct a theoretical and empirical analysis of loan loss reserves in the Polish listed banks in the period 2011- -2019 The research hypothesis states that there is a significant variation in the level of loan loss reserves among Polish listed banks in 2011-2019. The research covered 12 Polish banks listed on the Warsaw Stock Exchange. The empirical study is based on the Bank Focus database. Furthermore, the situation of reserves in the Polish banking sector before the start of the COVID-19 pandemic was assessed, as well as signalling the changes in the level of credit losses in the Polish banking sector during the pandemic. The analysed banks were differentiated according to their level of loan loss reserves, coverage ratio, and the ratio of the amount of loan loss reserve to the total value of net interest revenue. The research results can also be used as a benchmark for decisions and actions taken by the regulatory and supervisory authorities, and may increase the trust the stakeholders have in the banking sector.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 1, s. 14-29
Keywords: bank; safety; expected losses; provisions; loan loss reserves; bezpieczeństwo; oczekiwane straty; rezerwy; rezerwy na straty kredytowe